IMPLEMENTATION ANDROID ARCHITECTURE COMPONENT FOR DEVELOPING THE SIMLING APPLICATION (ENVIRONMENT MANAGEMENT SYSTEM) - Arafat, Doni; Defriani, Meriska; Kaniawulan, Ismi (RISTEC : Research in Information Systems and Technology, 2025)
Environmental management in Cluster Cahaya Mekar Wangi is still manual, utilizing WhatsApp and Excel for dues recording, financial reports, and security tracking, which often results in data errors and low transparency. This study developed SIMLING, an Android-based application, to digitalize and integrate these processes into a unified system. Built using the Waterfall model with Kotlin (frontend), Golang (backend), and MySQL in Docker (database), SIMLING offers real-time payment recording with receipt uploads, automated validations, transparent reports, QR-based security monitoring, and centralized notifications. The implementation shows SIMLING streamlines administrative tasks, improves transaction validation, and enhances security monitoring, while providing residents with easier payments and clear financial information. This supports smarter, more structured, and sustainable community management.